“Funciones ejecutivas en individuos menores de 18 años. centro de adolescentes infractores. Riobamba, 2019” - Calderón Zavala, Erika Gabriela (2020)
The present study had as its main objective the analysis of executive functions in individuals under 18 years of the Center of Infringing Adolescents. Riobamba, 2019. The study sample comprised 30 records of Adolescents in Conflict with the Criminal Law. The methodology used was documentary, bibliographic, non-experimental transverse design and descriptive level. The technique used was the observation, as an instrument the observation sheet was prepared where the sociodemographic data and performance results of the Neuropsychological Battery of Executive Functions and Frontal Lobes II (BANFE-2), reagent that was recently approved, were recorded. by the psychologist of the center Among the main results it is evident that 64.71% have a severe alteration performance, 23.53% moderate level alteration and only 11.76% reflect a normal performance in the Evaluation of Executive Functions. Regarding the performance of each area of the prefrontal, all three have similar percentages of alteration, predominantly with 93.33% of the dorsolateral area. Due to the percentage of alteration of the offending adolescents, the researcher developed neuropsychological rehabilitation strategies for executive functions, which, when reviewed and approved, may be applied by the Mental Health professional.